Um estudo de casos para auxílio à definição de um modelo de portabilidade na implementação de algoritmos simulados em robôs reais - Souza, Wanderson Gomes de (2014)
The development of algorithms oriented to robotic systems, in simulation environments, supports the identification and prediction of many problems before their tests in real environments. However, there is still not a process to ensure that an algorithm evaluated in a simulation platform will similarly work when migrated to real robots. The interference of several factors, such as engine and sensors properties, as well as the lack of a methodology that supports the interaction simulation/reality is considered as one of the main problems in this transition, so that there is a large conceptual development gap between real and simulated environments. This work aims to contribute with the formalization of a conceptual model to assist in the transition process, in which it is possible to highlight the peculiarities that require further attention from developers.. For that end, as a case study, it was developed an anti-collision algorithm, which involves several characteristics of a robotic system. Its implementation was carried out in both Unity3D simulator and real robots developed in the Arduino platform. The results were obtained and compared by a quantitative analysis of graphs using MATLAB. All necessary changes were classified and evaluated, raising up an initial idea of the transition model, which formalizes the main particulars of the project